Magnetic Order and Coupling Phenomena A Study of Magnetic Structure and Magnetization Reversal Processes in Rare-Earth-Transition-Metal Based Alloys and Heterostructures - Schubert, Christian (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2014)
This thesis presents recent developments in magnetic coupling phenomena of ferrimagnetic rare-earth transition-metal Tb-Fe alloys and coupled systems consisting of ferri-/ferromagnetic heterostructures. Taking advantage of the tunability of the exchange coupling between ferrimagnetic and ferromagnetic layers by means of stoichiometry of the Tb-Fe layer, the variable number of repetitions in the Co/Pt multilayer as well as the thickness of an interlayer spacer, it is demonstrated that large perpendicular unidirectional anisotropy can be induced at room temperature. This robust perpendicular exchange bias at room temperature opens up a path towards applications in spintronics.